Effect of non-thermal processing techniques on pathogenic and spoilage microorganisms of milk and milk products - SHABBIR, Muhmmad Asim; AHMED, Haassan; MAAN, Abid Aslam; REHMAN, Abdur; AFRAZ, Muhammad Talha; IQBAL, Muhammad Waheed; KHAN, Imran Mehmood; AMIR, Rai Muhammad; ASHRAF, Waqas; KHAN, Moazzam Rafiq; AADIL, Rana Muhammad (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2020)
Abstract Milk is a nutritious perishable product having a short shelf-life owing to the occurrence of spoilage bacteria in it. This has led to an increasing demand for ensuring safety through milk processing. Conventional techniques (such as heat treatment) increase shelf-life but damage the nutritional and sensory qualities of milk. Hence, there is a need to develop innovative, nonthermal processing techniques that increase the shelf-life while preserving its nutritional quality. This review focuses on the recent advances in assuring microbial safety of milk by using nonthermal techniques such as high-pressure processing, pulsed electric fields, ultrasound, ultraviolet irradiation and membrane microfiltration.